2013
DOI: 10.1021/la304836e
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Hydrophobic Drugs in Pluronic F127 Micelles: Effects of Drug Hydrophobicity, Solution Temperature, and pH

Abstract: Three drugs, Ibuprofen, Aspirin and Erythromycin, are encapsulated in spherical Pluronic F127 micelles. The shapes and the size distributions of the micelles in dilute, aqueous solutions, with and without drugs, are ascertained using cryo-Scanning Electron Microscopy and Dynamic Light Scattering (DLS) experiments, respectively. Uptake of drugs above a threshold concentration is seen to reduce the critical micellization temperature of the solution. The mean hydrodynamic radii and polydispersities of the micelle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
155
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(178 citation statements)
references
References 46 publications
(102 reference statements)
22
155
1
Order By: Relevance
“…Subsequently, the slides were submerged into 2% alcoholic eosin solution (Sigma) for 2 min. Slides were drained well, sections were dehydrated through an ascending alcohol bath series (30,50,70, 95 and 100 %, 1 min in each) and cleared in xylene (Sigma) for 2 min. Finally, the slides were allowed to air dry and were mounted in distrene plasticiser xylene mountant for histology (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the slides were submerged into 2% alcoholic eosin solution (Sigma) for 2 min. Slides were drained well, sections were dehydrated through an ascending alcohol bath series (30,50,70, 95 and 100 %, 1 min in each) and cleared in xylene (Sigma) for 2 min. Finally, the slides were allowed to air dry and were mounted in distrene plasticiser xylene mountant for histology (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Camptothecin (CPT; partition coefficient, logP ¼ 1.7) and its more potent derivative 7-ethyl-10-hydroxy-CPT (SN38; logP ¼ 2.7) were selected as model compounds for poorly water-soluble chemotherapy drugs. CPT-loaded liposomes were prepared with the cationic lipid 1,2-dioleoyl-3-trimethylammoniumpropane (DOTAP) 29 and SN38 was encapsulated into cetyltrimethylammonium bromide (CTAB) micelles 30 .…”
Section: T8-gfp-gb1mentioning
confidence: 99%
“…It has been reported that central metals within the cavity of the porphyrins change the hydrophobicity of the molecule. [28] It was also found that the most hydrophobic drugs increased the sizes of the micellar core and corona, [29] hence the increase in size of micelles containing metalated porphyrins compared to metal free ones could be a result of increased hydrophobicity of the former, while small differences in sizes for the micelles of metalated derivatives reflect small differences in hydrophobicity.…”
Section: Dynamic Light Scattering (Dls)mentioning
confidence: 99%
“…On approaching the CP many of these copolymer solutions exhibit sphere to rod transitions 8 . From all the Pluronics, F-127 has shown to be a very interesting one owing to its potential use as DDS [9][10][11] , removal of aromatic contaminants from industrial waste waters 12,13 , and in preparation of mesoporous materials [14][15][16] . Pluronic F-127 form spherical micelles where the core of the micelles consists of hydrophobic PPO blocks, whereas the corona is formed by hydrated PEO blocks 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Pluronic F-127 form spherical micelles where the core of the micelles consists of hydrophobic PPO blocks, whereas the corona is formed by hydrated PEO blocks 17 . The properties and potential application of these micelles as DDS has been studied by several groups 8,9,18,19 . The suitability of these polymers as drug carriers depends on key micelle properties, such as stability, loading capacity, and release kinetics.…”
Section: Introductionmentioning
confidence: 99%